How Should the Worldwide Knowledge of Traditional Cancer Healing Be Integrated with Herbs and Mushrooms into Modern Molecular Pharmacology? - Yulia Kirdeeva; Olga Fedorova; Alexandra Daks; Nikolai Barlev; Oleg Shuvalov (MDPI AG, 2022)
Traditional herbal medicine (THM) is a "core" from which modern medicine has evolved over time. Besides this, one third of people worldwide have no access to modern medicine and rely only on traditional medicine. To date, drugs of plant origin, or their derivates (paclitaxel, vinblastine, vincristine, vinorelbine, etoposide, camptothecin, topotecan, irinotecan, and omacetaxine), are very important in the therapy of malignancies and they are included in most chemotherapeutic regimes. To date, 391,000 plant and 14,000 mushroom species exist. Their medical and biochemical capabilities have not been studied in detail. In this review, we systematized the information about plants and mushrooms, as well as their active compounds with antitumor properties. Plants and mushrooms are divided based on the regions where they are used in ethnomedicine to treat malignancies. The majority of their active compounds with antineoplastic properties and mechanisms of action are described. Furthermore, on the basis of the available information, we divided them into two priority groups for research and for their potential of use in antitumor therapy. As there are many prerequisites and some examples how THM helps and strengthens modern medicine, finally, we discuss the positive points of THM and the management required to transform and integrate THM into the modern medicine practice.